Copper‐Mediated Direct Cyanatation of Benzamides: A New Approach to the Synthesis of Quinazolinediones. Issue 6 (5th February 2020) - Kianmehr, Ebrahim; Falahat, Mohammad Reza; Tanbakouchian, Arezoo; Mahdavi, Mohammad
Abstract : Copper mediated cyanatation of N‐ (quinoline‐8‐yl)benzamides with cyanate salts and subsequent intramolecular cyclization of the resulting product was accomplished. Different derivatives of quinazoline‐2, 4(1 H, 3 H )‐dione bearing quinoline‐8‐yl directing group were readily prepared in moderate to high yields by this methodology from easily accessible starting materials through cascade directed C–H bond functionalization/annulation reactions. Abstract : A practical, versatile, and efficient copper‐mediated direct cyanatation of C–H bonds of N ‐(quinoline‐8‐yl)benzamides by potassium cyanate for the synthesis of quinazoline‐2, 4(1 H, 3 H )‐dione derivatives has been described. Various derivatives of quinazoline‐2, 4(1 H, 3 H )‐dione bearing quinoline‐8‐yl directing group were readily prepared in moderate to high yields by this methodology from easily accessible starting materials